UJI TOTAL GLUKOSA DAN AKTIVITAS ANTIOKSIDAN BEBERAPA PRODUK PANGAN FUNGSIONAL BERBAHAN DASAR UBI JALAR UNGU (Ipomoea batatas L.) var AYAMURASAKI - Edysri Hermayudha P; Munifatul Izzati; Endang Saptiningsih (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Functional food is food with high nutrition and important to illness terapy. Functional food product based of purple sweet potato are an alternative to replace primary food. This research purpose to know the quantity of total glucose, antioxydant activity, and antosianin decreaseful colour in a few of functional food product based of purple sweet potato. This research take place in food technology laboratoryum Unika Semarang on Desember until January 2013. This research use RAL single factor of food making process include milk, ice cream, wet noodle, dry noodle, and flour look for quantity of total glucose, antioxidant activity, and antosianin decreaseful colour. Method of research include analyse quantity of total glucose assay fenol method, antioxidant activity assay Diphenyl Pycril Hydriazil (DPPH), and observation in antosianin decreaseful colour product. The result of research show that the best food product is purple sweet potato flour. That product has quantity of total glucose 2,805 g/100 g, IC50 - 49951 %, and antosianin colour product take no damage because it still look purple. Keyword: the functionality food product, total glucose quantity, antioxydant activity IC50, antosianin decreaseful colour